Banking Cybercrime as One of the Main Problems of Modern Society - K. A. Kovtun (Теоретическая и прикладная юриспруденция)
This article examines the specifics of banking cybercrimes, their victims, as well as criminals who commit these crimes. The research method is based on statistical data from the Bank of Russia. The author concludes that improving the economic and legal literacy of the population is the most effective way to reduce the trend of banking cybercrime.